PENGARUH DISIPLIN KERJA GURU DAN LOYALITAS GURU TERHADAP KOMITMEN GURU SEKOLAH DASAR NEGERI DI KECAMATAN TANJUNG MEDAN KABUPATEN ROKAN HILIR - Suprapto Suprapto; Fadly Azhar; Sumarno Sumarno (STKIP Pesisir Selatan, 2022)
This study aims to determine the effect of variables (1) teacher work discipline on teacher commitment, (2) teacher loyalty to teacher commitment, (3) teacher work discipline and teacher work discipline and teacher loyalty together with teacher commitment. The research respondents were State Elementary School teachers in Tanjung Medan District, Rokan Hilir Regency, totaling 118 people with a sample of 91. The data was collected through questionnaires as a research instrument. The data analysis used is descriptive analysis and inferential statistical analysis. The instrument reliability coefficient was calculated using the Cronbach alpha formula. The results showed that there was a positive and significant effect of teacher work discipline on teacher commitment of 0.470, and there was a positive and significant effect of teacher loyalty on teacher commitment of 0.555. Meanwhile, together there is an effect of teacher discipline and teacher loyalty on teacher commitment of 0.477.